2005
DOI: 10.1007/s10886-005-4243-3
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedants against Hylobius abietis Pine Weevils: An Active Compound In Extract of Bark of Tilia cordata Linden

Abstract: Linden (Tilia cordata) bark was shown to contain an antifeedant effective against the large pine weevil, Hylobius abietis. Soxhlet extraction of inner and outer bark resulted in an extract that showed antifeedant activity in a microfeeding assay. The extract was fractionated by chromatography on silica gel using gradient elution with solvents of increasing polarity. The content of the fractions obtained was monitored by thin layer- and gas chromatography. Fractions of similar chemical composition were merged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Of these, nonanoic acid was found in a dichloromethane/methanol bark extract of Tilia (Månsson 2005;Månsson et al 2005). In addition, hexanoic, heptanoic, octanoic, and nonanoic acids have been found in Fagus wood (Guillén and Ibargoitia 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, nonanoic acid was found in a dichloromethane/methanol bark extract of Tilia (Månsson 2005;Månsson et al 2005). In addition, hexanoic, heptanoic, octanoic, and nonanoic acids have been found in Fagus wood (Guillén and Ibargoitia 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only young plant material (second-year shoots and branches) was used. Preparation and extraction of the bark were performed as previously described (Månsson 2005;Månsson et al 2005). Prior to removal of bark from twigs, the total bark area was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Recent development of a trap that exploits the insects' feeding behaviour, however, has improved the acquisition of test specimens (Klingenberg et al, 2009; Björklund, 2009) compared with previous methods (Cerezke, 1994). Information on feeding preferences among different hosts is important for developing appropriate silvicultural recommendations, developing host inventories for trade records as wood product and insect movement increases, and deriving new antifeedant control strategies, as has been proposed for H. abietis with deciduous trees (Leather et al, 1994; Månsson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…contains compounds which inhibit feeding activity of the large pine weevil. In further studies, carboxylic acid, limonene, carvone, and verbonen compounds, which demonstrated antifeedant activity against H. abietis in laboratory experiments, were isolated from extracts of T. cordata bark [109].…”
Section: Botanical Antifeedantsmentioning
confidence: 99%